Breaking bad news of cancer diagnosis - The cancer patients'perception in Serian District - Mathew, Anak Gabriel Bain (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This study aimed to assess the perceptions of cancer patients on the breaking of bad ever news of cancer diagnosis. The research method used was a cross sectional study on cancer patients in Serian district using Breaking bad news Assessment Scedule (BAS) questionnaire. It was conducted using snowballing sampling among cancer patients in Serian district. Face to face interview was conducted after the consent was obtained.Data was entered and analyzed using SPSS version 19. A total of 134 patients participated in this study. Majority were comfortable with the current method of breaking bad news. The main aspects found were, the importance usage of body language, management of time and identifying patients'key area of concerns.